Desafios da gestão de pessoas nos processos de contratualização: o caso do Hospital Municipal Infantil Menino Jesus - Jorge, Ilza Valéria Moreira (2012)
The scope of this paper is to analyze Human Resources Management, within the contracting process. According to this strategy, the State transfers to a social organization the management of a public equipment, based on a 'Management Agreement' signed with such organizations. The model described here has been adopted by the City of São Paulo (Municipal Law 14.132/2006) and by other public administrations throughout the country, in order to improve efficiency and quality of the Health System. The case in point is that of Hospital Municipal Infantil Menino Jesus (HMIMJ), which has been managed by Instituto de Responsabilidade Social Sírio Libanês (IRSSL) since November 2008. This specific experience in São Paulo is innovative, especially in comparison to the work carried out by the Government at the State level, since it refers to the implementation of a management agreement at a unit which is already operating. In this situation civil service professionals will work side by side with new employees hired by the Social Organization (OS). The aim of this study is to propose measures to improve the Human Resources Management at HMIMJ, thus achieving simultaneously increased efficiency and greater involvement of all employees, taking into account the background theory on Social Organizations. Through interviews, field visits, and the data provided, the paper shows in detail how different work contracts coexist in the institution studied. Finally, some suggestions are given for improving the Human Resources Management at HMIMJ, taking into account the existence of a hybrid institutional model.